2022
DOI: 10.2298/tsci2203499z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on the bubble-electrospinning process and its hints for 3-D printing technology

Abstract: The temperature will significantly affect the surface tension of a bubble. By suitable control of the inside and outside temperature of the spun bubble, the surface tension can be vanished entirely. This zero-tension phenomenon is extremely helpful in the bubble electrospinning process. An experiment is designed to study the effect of the inside and outside temperature on the nanofibers diameter, and the theoretical prediction agrees well with the experimental data. This paper sheds a bright … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Liff et al 22 and Zuo and Liu 23 pointed out that the ordered arrangement of the internal structure of nanofibers had a great relationship with the reduction of the diameter. Combining with the law of conservation of mass and using MATLAB software (Math Works), the fiber diameter tested was fitted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Liff et al 22 and Zuo and Liu 23 pointed out that the ordered arrangement of the internal structure of nanofibers had a great relationship with the reduction of the diameter. Combining with the law of conservation of mass and using MATLAB software (Math Works), the fiber diameter tested was fitted.…”
Section: Resultsmentioning
confidence: 99%
“…The average density of the spinning solution was determined to be 2.562 (±0.35) kg/m 3 , while the injection speed was set to 0.8 ml/h and the inner diameter of the long needle was 0.7 mm. According to formula (1), the Reynolds number of 15% PVDF/DMF spinning solution in the long needle was calculated as follows 23 :…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spider spinning process is extremely captivating for many scientists, because the properties of the spider silk is inextricably linked with its spinning process. 1,2 The bubble electrospinning 3,4 was invented by inspiration of the spider spinning, and 3-D printing technology [5][6][7][8][9] can be optimized by spider's web design. It was reported that the spider spinning has the attractive property of minimal energy consumption, 2 the energy saving 10,11 and energy harvesting 12,13 are two key factors for a green earth.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The bubble electrospinning 3,4 was invented by inspiration of the spider spinning, and 3-D printing technology [5][6][7][8][9] can be optimized by spider's web design. It was reported that the spider spinning has the attractive property of minimal energy consumption, 2 the energy saving 10,11 and energy harvesting 12,13 are two key factors for a green earth. Spider silk has many advantages, such as high elasticity, high toughness, high water absorption, light weight and biodegradability, which make it in many fields, such as aerospace (structural materials and composite materials of artificial satellites and space suits), military (tanks, armor, aircraft, bulletproof vests and parachutes), industrial (high-strength materials, wheel casings, etc.)…”
Section: Introductionmentioning
confidence: 99%